Linking knowledge to action in ocean ecosystem management: The Ocean Modeling Forum - Tessa B. Francis; Phillip S. Levin; Andre E. Punt; Isaac C. Kaplan; Anna Varney; Karma Norman (Elementa: Science of the Anthropocene, 2018)
The sustainable use of global marine resources depends upon science-based decision processes and systems. Informing decisions with science is challenging for many reasons, including the nature of science and science-based institutions. The complexity of ecosystem-based management often requires the use of models, and model-based advice can be especially difficult to convert into policies or decisions. Here, we suggest five characteristics of model-based information and advice for successfully informing ocean management decision-making, based on the Ocean Modeling Forum framework. Illustrated by examples from two fisheries case studies, Pacific sardines 'Sardinops sagax' and Pacific herring 'Clupea pallasii', we argue that actionable model-based output should be aspirational, applicable, parsimonious, co-produced, and amplifying.